2012
DOI: 10.1029/2012gl051942
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of an Earth system climate model to idealized radiative forcing

Abstract: We diagnose forcing and climate feedbacks in benchmark sensitivity experiments with the new Met Office Hadley Centre Earth system climate model HadGEM2‐ES. To identify the impact of newly‐included biogeophysical and chemical processes, results are compared to a parallel set of experiments performed with these processes switched off, and different couplings with the biogeochemistry. In abrupt carbon dioxide quadrupling experiments we find that the inclusion of these processes does not alter the global climate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 18 publications
4
28
1
Order By: Relevance
“…Total cloud cover increases in all five scenarios with no strong dependency on the forcing agent (not shown), but most CMIP3 and CMIP5 models actually show a decrease in total cloud cover (Bender, 2011;Andrews et al, 2012). Gregory and Webb (2008) as well as Andrews and Forster (2008) showed that fast cloud adjustments caused by an increase in CO 2 forcing are responsible for most of the spread among models.…”
Section: Changes In the Hydrological Cyclementioning
confidence: 94%
“…Total cloud cover increases in all five scenarios with no strong dependency on the forcing agent (not shown), but most CMIP3 and CMIP5 models actually show a decrease in total cloud cover (Bender, 2011;Andrews et al, 2012). Gregory and Webb (2008) as well as Andrews and Forster (2008) showed that fast cloud adjustments caused by an increase in CO 2 forcing are responsible for most of the spread among models.…”
Section: Changes In the Hydrological Cyclementioning
confidence: 94%
“…An increasing stomatal closure under high CO 2 affects the balance of latent and sensible heat fluxes from plant canopies and thereby (among other effects) reduces the formation of low-level clouds (Sellers et al 1996;Doutriaux-Boucher et al 2009;de Arellano et al 2012). Moreover, vegetation cover changes and increasing leaf area due to CO 2 fertilization can lead to surface albedo modifications and changes in dust mobilization (Zickfeld et al 2011;Andrews et al 2012). All of these processes change the radiative balance within the atmosphere and establish a radiative forcing that leads to surface warming (DoutriauxBoucher et al 2009).…”
Section: Experiments Description and Analysis Methodsmentioning
confidence: 99%
“…HadGEM2-ES has the 2nd highest equilibrium climate sensitivity of any of the CMIP5 models at 4.6 °C (Andrews et al 2012b). This value is also substantially higher than HadCM3 for which the value is closer to 3.7 °C (e.g.…”
Section: Implications For the Climate In Response To Increased Comentioning
confidence: 99%